Techniques frequently used during London Olympic judo tournaments: a biomechanical approach - Sterkowicz, S.; Sacripanti, A.; Sterkowicz-Przybycien, K. (Archives of Budo, 2013)
Background and Study Aim. Feedback between training and competition should be considered in athletic training. The aim of the study was contemporary coaching tendencies in women`s and men`s judo with particular focus on a biomechanical classification of throws and grappling actions. Material and Methods. 359 throws and 77 grappling techniques scored by male and female athletes in Olympic Judo Tournaments (London 2012) have been analyzed. Independence of traits (gender and weight category by technique classes) was verified via ?2 test. Comparison between frequency of each subsequent technique class and rest/inconclusive counts was made in 2 x 2 contingency tables. The significance level was set at p < 0.05. Results. Throwing technique frequencies grouped in the seven biomechanical classes were dependent on gender. A significant difference was found between frequencies of variable arm of physical lever technique scored by males (27.09 %) and females (16.67 %) as compared to the rest/inconclusively techniques counts. Significant differences between men who competed in extra lightweight and heavy weight concerned the frequency of the techniques used with maximum arm or variable arm of physical lever and a couple of forces applied by trunk and legs. In females, a tendency to higher frequency of techniques that used couple of forces applied by arm or arms and leg was observed in extra lightweight compared to the heavy weight. Conclusion. Because the technique preferred in the fight depends on a gender and weight category of a judoka, the relationships found in this study, which can be justified by the biomechanics of throws, should be taken into consideration in technical and tactical coaching of the contestants. A method used in this study can be recommended for future research concerning coaching tendencies.